Firestorm Response: Managing Brand Reputation during an nWOM Firestorm by Responding to Online Complaints Individually or as a Cluster. Issue 2 (3rd April 2018) - Lappeman, James; Patel, Mukund; Appalraju, Raeshaan
ABSTRACT: This study provides evidence of how marketers should respond to a sudden discharge of negative word-of-mouth (nWOM) communication that spreads rapidly across social media platforms, known as an online "firestorm." The study aimed to determine whether a company's response policy during an online firestorm influenced their brand reputation among observers of the firestorm. An experiment offered three different company approaches to the firestorm. The study used a conclusive quantitative design by manipulating independent variables in a controlled environment in order to infer causality through an online survey to 300 participants. The study shows that when faced with the option of replying to a cluster of complaints or each individual complaint, a more positive brand reputation is engendered through individual replies. While research in digital marketing has progressed to provide companies with strategies to use digital platforms as a marketing tool, the negative side of social media—in this case online firestorms—is still largely left unattended. Addressing the direct issue of how to respond to online firestorms is therefore of significant relevance to marketing practitioners and academics.